THE EXISTENCE OF CIRCULAR LETTER IN INDONESIA STATE LAW STUDY ON CIRCULAR LETTER NUMBER: 21 /SE/SATGAS/2021 CONCERNING GUIDELINES FOR IMPLEMENTATION OF COMMUNITY ACTIVITIES RESTRICTIONS (PPKM) LEVEL 2 IN PEKANBARU CITY - M. Alpi Syahrin (NOMOI Law Review, 2022)
The existence of circulars in the Indonesian legal state is part of the policy regulations as further elaboration, both technically and administratively. The presence of Circular Number: 21 /SE/SATGAS/2021 concerning Guidelines for the Implementation of Level 2 Community Activity Restrictions (PPKM) in Pekanbaru City is a form of: Implementing the Instruction of the Minister of Home Affairs Number 44 of 2021 and Instruction of the Governor of Riau Number 198/INS/HK /2021 and the form of a pandemic emergency condition to limit the massive spread aimed at the Head of Pekanbaru City Government/Private /BUMN/BUMD Institutions, Heads of Regional Apparatuses in the Pekanbaru City Environment, Heads of Private Offices/Associations/Entrepreneurs, Heads of Sub-City Heads/Lurah Pekanbaru and Pekanbaru City Community.Keywords: Government, Policy Regulation, Circular